Experimental Study on the Properties of Autoclave Curing High-Strength Concrete According to CaO/SiO2 Ratio - Jeongmin Ra; Sangchul Shin; Jinman Kim (Applied Sciences, 2023)
In this experimental study, tests were conducted to obtain the CaO/SiO2 (C/S) molar ratio that minimizes the micropores of hardened concrete. To this end, the compressive strength, thermogravimetric analysis (TGA), and microporous structure of hardened concrete were investigated using concrete specimens made with silica fume and quartz powder under high-temperature/high-pressure conditions. The tests yielded the following results: (1) the highest compressive strength (200 MP) was exhibited in the C/S molar ratio range of 0.7–0.9, and lower compressive strength was exhibited in the C/S molar ratio ranges of ≤ 0.6 and ≥ 0.95; (2) the productivity of calcium silicate hydrate (C-S-H) tended to increase in proportion to the C/S molar ratio in all specimens; (3) the microstructure was measured using mercury intrusion porosimetry (MIP), and the maximum total porosity of specimens was calculated to be 10%. As the C/S molar ratio increased, the total porosity decreased, as did the pore diameter and threshold pore diameter. Thus, C/S molar ratio was found to be a major factor affecting the compressive strength and microporous structure of autoclave-cured cement and the optimal mechanical properties were exhibited in the C/S molar ratio of 0.8–0.9. However, the reactivity varies depending on the material used and curing conditions employed. Therefore, the hydration products obtained using the curing conditions need to be investigated further.